Estudos bioeletroquímicos de compostos biologicamente ativos: derivados da β-Lapachona e ácido úsnico - Vasconcelos, Camila Calado de (2011)
Synthetic derivatives of β-lapachone and usnic acid are of particular interest as biologically active substances. This study aims to seek information that suggest a biological mechanism of action. Electrochemical experiments of the compounds mentioned above were performed in different condictions, protic and aprotic media, as well as with relevant biological targets. In this case, DNA and experiments with molecular oxygen were performed since a mechanism involving redox cycling with oxygen after the reduction process is widely activity reported for quinones. A physical-chemical characteristic displayed by these compounds is low solubility in water, something very relevant to pharmacological action. Thus, studies were performed with cyclodextrin, an oligosaccharide glycoside to investigate the possibility of formation of inclusion complex, resulting in increased solubility of the same. The voltammetric behavior of the four derivatives of β-lapachone were compared and showed that changes in substituent did not affect the reduction process. The compounds of the series LAUSEST had similar characteristics to the behavior of quinones in protic and aprotic media, and showed, like its precursor, β-lapachone, reactivity with oxygen, suggesting that cytotoxic activity may be related to ROS . The interaction of compounds with β-CD and HP-β-CD in solution, observed by cyclic voltammetry showed that the presence of these host molecules, demonstrated changes in the voltammetric profile of each substance, suggesting an increase of solubility. Moreover, there was a possible use of the modified electrode with SAM mixed β-CD-SH-Au + MUA, as a sensor for determination of β-lapachone in clinical analysis and quality control step. Studies with ssDNA showed the presence of interaction of analytes with the bases guanine and adenine. However, studies with dsDNA biosensor showed no interaction, implying a likely biological mechanism of action related to alkylation of DNA, emphasizing the importance of voltammetric techniques for biological analysis.